(3eONd GdfXes - (3ShfjG eMeO(B, (3GdHcQjs ((3GdEScfOQjI(B:s (3GdOGQ GdLGeYjI(B,s, 2001)
(3GdJWhQ GdJGQjNj dEOGQI GdEfJGL hGdYedjGJ(B- (3EOGQI GdfXe GdEfJGLjI(B- (3Gdeaghe hGdhXGFa(B- (3GdJfHD(B- (3GdeaGgje GdGSGSjI ddLhOI(B- (3GdJNWjW GdELeGdj(B- (3JUeje GdefJLGJ(B- (3JNWjW GdYedjGJ GdEfJGLjI(B- (3ehbY GdJSgjdGJ GdEfJGLjI(B- (3GdJQJjH GdOGNdj ddJSgjdGJ GdEfJGLjI(B- (3LOhdI GdYedjGJ(B- (3GdJMSjf GdeSJeQ ddYedjGJs
Keywords: (3EOGQI GdEfJGLs; (3GdEfJGLs